ANALISIS MODAL KERJA PADA BUDIDAYA IKAN NILA BAPAK SUPIYANI DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Berlina, Iin; Saher, Sayid; Dewi, Septira (I-Con Media, 2024)
This research is qualitative research and the sampling technique is purposive sampling using 10 respondents each. Based on the results of research conducted by researchers on Mr. Supiyani's Tilapia Fish Cultivation business, namely (1) Mr. Supiyani's Tilapia Cultivation Business in 2021 earned a profit of IDR. 54,690,000,- and in 2022 will get a profit of Rp. 63,747,000,- this profit has increased by Rp. 9,057,000,- (2) The source of working capital for Mr. Supiyani's Tilapia Cultivation business in 2021 and 2022 is capital of IDR. 7,264,000,- Plus depreciation of Rp. 100,000,- so the total is Rp. 7,364,000,- (3) The use of working capital in Mr. Supiyani's Tilapia Cultivation business is to purchase equipment amounting to Rp. 550,000,- (4) The increase in working capital for Mr. Supiyani's Tilapia Cultivation business is IDR. 6,814,000,-. To test the analytical tools used, it is necessary to present financial report data. Specifically, the financial data collected by researchers was only through interviews with owners without any recorded evidence because the business owners did not have complete financial reports in the form of profit and loss and balance sheets.